Masyarakat dan Kebudayaan Sekolah - Sihaloho, Wardani; Haniyah, Cut Nurul; Yani, Rahma; Hayati, Nurlaila; Harahap, Hotma Sari; Yulianti, Nisafira (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
The importance of the relationship between society and school culture is to create a healthy balance between these two entities. A school culture that is positive and relevant to the surrounding community can help students develop themselves and contribute positively to society. Conversely, positive influences from the community can also shape an inclusive and adaptive school culture. The method used in this paper is a qualitative approach with the type of writing analytic descriptions. The author will explain and analyze the problems encountered in the topic raised. Society can influence school culture in various ways such as providing support for school programs, providing input on school policies, and influencing student behavior outside of school. Society and school culture are two things that are interrelated and influence one another. These changes were mainly due to the implementation of the 2013 Curriculum which emphasized more active and creative learning. Keywords: Society, Change, Culture, School.